Entrepreneurial University Campus Ecosystem (EUCE) Design with Interpretive Structural Modelling - M.R. Meigounpoory; A. Arabiun; M.M. Poorbasir; A. Mobini Dehkordi (Fanāvarī-i āmūzish, 2019)
Background and Objective:  In recent years, in addition to educational and research missions, attention to entrepreneurship has increased in universities and scientific centers around the world, and therefore entrepreneurship training courses have been expanded in them. Evidence shows that environmental support and creating an appropriate environment for the effectiveness of the education system and educational technologies in the creation and development of businesses can have an effective impact on their entrepreneurial path. The entrepreneurial ecosystem is defined as the close relationship between individuals, the government and its affiliated institutions, and other influential components to support entrepreneurial activities in a particular geographical area. This ecosystem may be regional or national, or even university-level. The study of the higher education policies for university entrepreneurship ecosystem creation has become one of the major new and important topics in the field of higher education and university entrepreneurship ecosystems. Hence, changing the approach from purely educational and research planning to the establishment of the university campus entrepreneurship ecosystem has been attended by the world's leading universities. Current paper aims to design a model for creating an Entrepreneurial University Campus Ecosystem (EUCE) with the configuration and leveling of the factors. Methods: Hence using a qualitative approach, an in-depth and exploratory interview was conducted with 20 experts from the research population. Findings: Then, using open and axial coding method, 9 axial factors were identified. The axial factors affecting the creation of Entrepreneurial University Campus Ecosystem (EUCE) have been classified using an Interpretive Structural method. A questionnaire was designed and distributed among 28 academic and field experts. A group of five experts on EUCE has studied the completed questionnaires and determined the relations between subject to disagreement components. Then, Interpretive Structural Modelling was built using Matlab software to develop an EUCE model. Conclusion: The results showed that the factor of promoting the culture of entrepreneurship ecosystem on campus, despite being an internal factor of the university, will play a very important role in creating an entrepreneurial ecosystem on campus (as an example of society) and developing an individual entrepreneurial culture. Corporate entrepreneurship culture and organizational entrepreneurship culture within the university will play an important role in improving the level of readiness to develop the university entrepreneurship ecosystem. In addition, improving university policies and laws, creating and expanding the infrastructure needed to create a university entrepreneurship ecosystem, improving the level of policy and management of university financial resources, increasing the intensity and level of research and development in the university ecosystem, have a great impact on creating an entrepreneurial ecosystem on campus. The new approach presented in the higher education system based on the new model of entrepreneurship ecosystem of the university campus presented in this article will be useful for all managers of the Ministry of Science, Research and Technology and the heads and boards of universities and researchers interested in developing higher education in Iran and other developing countries.   ===================================================================================== COPYRIGHTS  ©2019 The author(s). This is an open access article distributed under the terms of the Creative Commons Attribution (CC BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, as long as the original authors and source are cited. No permission is required from the authors or the publishers.  =====================================================================================